2023
DOI: 10.1002/cctc.202201172
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Rare Earth (R) Element in Ru‐supportedRScSi Electride‐like Intermetallic Catalysts for Ammonia Synthesis at Low Pressure: Insight into NH3Formation Mechanism

Abstract: This study investigates the influence of the rare-earth (R) element in Ru/RScSi electride-like intermetallic catalysts for ammonia synthesis under mild conditions (300-450 °C; 1-5 bar). All materials present poor specific surface area and the grain size impacts the ammonia yield. The catalytic performances follow the La to Gd lanthanides series (Ru 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…In addition, interactions between Ru and the TM from the support matrix (Co, Fe or Mn) also play an important role in the Ru dispersion and particle size, and in the global kinetic mechanism as well, given that the presence of a second active center is reported for these catalysts: while N 2 dissociation takes place on Ru sites, hydrogenation of N * dissociated atoms to form NH x species occurs over La surfaces [64]. On the other hand, single-phase LaRuSi intermetallic material was reported as an efficient catalyst for ammonia synthesis [65], since stronger chemical bonds between Ru and La are assumed to improve the electron transfer [63], whose activity is attributed to a dual behavior as an electride material, similarly to aforementioned intermetallic supports [24,[61][62][63], as well as the reversible exchange between lattice hydride ions and anionic electrons that takes place [65], leading to an activation energy as low as 40.4 kJ•mol −1 . Further investigations concluded that (La,Ce,Pr)RuSi intermetallics show an excellent stability to air and moisture [66], with no relevant changes in ammonia synthesis rate after half a year of exposure to ambient air during the storage of the material.…”
Section: Historical Evolution Of Catalysts For Ammonia Synthesismentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, interactions between Ru and the TM from the support matrix (Co, Fe or Mn) also play an important role in the Ru dispersion and particle size, and in the global kinetic mechanism as well, given that the presence of a second active center is reported for these catalysts: while N 2 dissociation takes place on Ru sites, hydrogenation of N * dissociated atoms to form NH x species occurs over La surfaces [64]. On the other hand, single-phase LaRuSi intermetallic material was reported as an efficient catalyst for ammonia synthesis [65], since stronger chemical bonds between Ru and La are assumed to improve the electron transfer [63], whose activity is attributed to a dual behavior as an electride material, similarly to aforementioned intermetallic supports [24,[61][62][63], as well as the reversible exchange between lattice hydride ions and anionic electrons that takes place [65], leading to an activation energy as low as 40.4 kJ•mol −1 . Further investigations concluded that (La,Ce,Pr)RuSi intermetallics show an excellent stability to air and moisture [66], with no relevant changes in ammonia synthesis rate after half a year of exposure to ambient air during the storage of the material.…”
Section: Historical Evolution Of Catalysts For Ammonia Synthesismentioning
confidence: 98%
“…A recent alternative to nitrides, hydrides, electrides and rare earth-based oxides can be found in the use of intermetallic compounds, whose understanding is of outstanding interest since they have promising properties in the field of catalyst design for many different applications and particularly for ammonia synthesis [24,[61][62][63]. Intermetallic materials can be used indistinctly as supports for Ru or as a compact catalyst where the TM is located in the intermetallic matrix.…”
Section: Historical Evolution Of Catalysts For Ammonia Synthesismentioning
confidence: 99%
“…Intermetallic RETM compounds are currently gaining attention as ammonia synthesis catalysts since the close interaction between RE and TM promotes N 2 dissociation efficiently. RETM x alloys ( x = 2, 3, 5) have been found useful for several applications, , particularly as hydrogen storage materials, in virtue of their ability to reversibly form hydrogenated complexes.…”
Section: Introductionmentioning
confidence: 99%